2018
DOI: 10.1136/oemed-2018-105114
|View full text |Cite
|
Sign up to set email alerts
|

Current research priorities for UK occupational physicians and occupational health researchers: a modified Delphi study

Abstract: Manganese (Mn) is a known neurotoxicant, and given its health effects and ubiquitous nature in metal-working settings, identification of a valid and reproducible biomarker of exposure is of interest. Global metabolomics were previously utilised to determine metabolites that differ between occupational groups defined by Mn exposure status, in hopes of informing a biomarker of exposure. Nine metabolites were found to differ between exposure groups in urine samples collected October 2014. To test the reproducibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…It did so by exploring the challenges in correctly measuring three effects that are typically not encountered (or deemed less relevant) in other healthcare domains: Productivity losses, intangible effects, and effects of the legal and fiscal context. As such, it contributes to previous work [ 8 , 15 ] that offered broader methodological guidelines in OHS, and it answers to the call for more research on economic evaluation in occupational health [ 70 ].…”
Section: Discussionmentioning
confidence: 66%
“…It did so by exploring the challenges in correctly measuring three effects that are typically not encountered (or deemed less relevant) in other healthcare domains: Productivity losses, intangible effects, and effects of the legal and fiscal context. As such, it contributes to previous work [ 8 , 15 ] that offered broader methodological guidelines in OHS, and it answers to the call for more research on economic evaluation in occupational health [ 70 ].…”
Section: Discussionmentioning
confidence: 66%
“…It appears from reviews published in EJWOP and other reviews I have read (and conducted) that cost effectiveness/return on investment type analyses are often absent from many systematic reviews. This impression is borne out at least in the health and wellbeing field by a recent study indicating such economic considerations are a research priority identified by occupational health professionals (Lalloo, Demou, Smedley, Madan, Asanati & Macdonald, 2018). Going forward, it would be helpful if systematic reviews and primary intervention studies were to give more attention to these economic considerations.…”
Section: Other Things To Consider In Systematic Reviewsmentioning
confidence: 99%
“…A systematic search of the literature revealed limited evidence regarding these issues (e.g. Coggon, 2005;Hotopf and Wessely, 2005;Lalloo et al, 2019a;Lalloo et al, 2019b;Lalloo et al, 2018;Rushton and Betts, 2001). This study hence aimed to identify current challenges and facilitators of OE research in the UK, and to assess the perceived impact of the challenges.…”
Section: Introductionmentioning
confidence: 99%